Analisis Faktor-Faktor yang Mempengaruhi Keberhasilan Posyandu dalam Meningkatkan Kualitas Pelayanan Kesehatan di Posyandu Sejahtera Kabupaten Tanah Datar - Haya Aqilah; Rahmadhona Fitri Helmi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the factors influencing the success of Posyandu Sejahtera in improving maternal and child healthcare service quality in Tanjung Barulak Village, Tanah Datar Regency. Informants were selected using a purposive sampling technique and consisted of Posyandu cadres, Posyandu administrators, healthcare personnel from the community health center (Puskesmas), and community members as service beneficiaries. Data were collected through semi-structured interviews and documentation and were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the success of Posyandu Sejahtera is influenced by four interrelated factors: Posyandu cadres, community participation, healthcare personnel, and facilities and infrastructure. Active and competent Posyandu cadres, high community participation, guidance and assistance from healthcare personnel, and adequate facilities and infrastructure despite several existing limitations collectively support the improvement of maternal and child healthcare service quality. These four factors work synergistically to enable Posyandu Sejahtera to deliver quality healthcare services.